BCL6 inhibition: a promising approach to prevent germinal center-driven allo-immune responses - Kraaijeveld, Rens; Hesselink, Dennis A.; Steines, Louisa; Heidt, Sebastiaan; Baan, Carla C. (Frontiers in Immunology, 2025)
After solid organ transplantation, antibody-mediated rejection (AMR) is the most important cause of late allograft loss. Central in this process are donor-specific antibodies (DSAs) targeting mismatched Human Leukocyte Antigens (HLA) on recipient endothelial cells. Alloreactive B cells can directly bind to mismatched HLA molecules expressed by endothelial cells of a transplanted organ through their B cell receptor. Upon antigen recognition, B cells can differentiate into memory B cells and plasma cells producing class switched, high affinity DSAs. Cognate interaction between alloreactive follicular T helper cells (Tfh) and B cells, both expressing the transcription factor BCL6, is essential for long-lived plasma cell formation. Blockade of BCL6 by inhibitory compounds has emerged as a promising therapeutic strategy in the treatment of BCL6-expressing B cell lymphomas. Beyond its direct cytotoxic effects on malignant B cells, BCL6 inhibition also disrupts the function of germinal center B cells and impairs survival and activation of Tfh cells after immunization. These findings suggest that BCL6-targeting therapies may have potential as an immunosuppressive strategy in the context of organ transplantation, where controlling the humoral allo-immune response is essential to prevent graft rejection. This article reviews the mechanisms by which BCL6 controls Tfh and B cell differentiation and germinal center formation after organ transplantation. Finally, it outlines how newly discovered BCL6 inhibitory compounds might intervene with these B cell mediated immune responses.